Surgical management of epilepsy due to cerebral cavernomas using neuronavigation and intraoperative MR imaging. (1st December 2013) - Sommer, Bjoern; Kasper, Burkhard Sebastian; Coras, Roland; Blumcke, Ingmar; Hamer, Hajo Martinus; Buchfelder, Michael; Roessler1, Karl
<x xml:space="preserve">Abstract</x> Objectives: Cure from seizures due to cavernomas might be surgically achieved dependent on both, the complete removal of the cavernoma as well as its surrounding hemosiderin rim. High field intraoperative MRI imaging (iopMRI) and neuronavigation might play a crucial role to achieve both goals. We retrospectively investigated the long-term results and impact of intraoperative 1·5T MRI (iopMRI) and neuronavigation on the completeness of surgical removal of a cavernous malformation (CM) and its perilesional hemosiderin rim as well as reduction of surgical morbidity. Methods: 26 patients (14 female, 12 male, mean age 39·1 years, range: 17-63 years) with CM related epilepsy were identified. Eighteen patients suffered from drug resistant epilepsy (69·2%). Mean duration of epilepsy was 11·9 years in subjects with drug resistant epilepsy (n = 18) and 0·3 years in subjects presenting with first-time seizures (n = 8). We performed 24 lesionectomies and two lesionectomies combined with extended temporal resections. Seven lesions were located extratemporally. Results: Complete CM removal was documented by postsurgical MRI in all patients. As direct consequence of iopMRI, refined surgery was necessary in 11·5% of patients to achieve complete cavernoma removal and in another 11·5% for complete resection of additional adjacent epileptogenic cortex. Removal of the hemosiderin rim was confirmed by iopMRI in 92% of patients. Two patients suffered from mild (7·7%) and one from moderate (3·8%) visual field deficits. Complete seizure control (Engel class 1A) was achieved in 80·8% of patients with a mean follow-up period of 47·7 months. Discussion: We report excellent long-term seizure control with minimal surgical morbidity after complete resection of CM using our multimodal approach.